Multi-dimensional constraint-based coal mining machine cutting path planning technology - Shuyang SONG; Shibo WANG; Yun WANG; Lijie WANG; Dongshuai SONG (Meitan xuebao)
The cutting path planning technology for coal mining machines is one of the key technologies for achieving intelligent mining in fully mechanized mining faces. Existing cutting path planning techniques do not fully consider the adaptability of mining equipment in the cutting space, and lack comprehensive consideration of the constraints in four dimensions, namely the roof and floor of the mining seam, the direction of the mining face, and the advancing direction of the mining face. To address this issue, this paper proposes a cutting path planning method for coal mining machines that integrates geological characteristics of the coal seam and multidimensional constraints of the mining equipment’s posture. First, based on the operational requirements of the fully mechanized mining face, a cutting space constraint model is established with the posture of hydraulic supports, scraper conveyors, and coal mining machines as the constraint conditions. This model enables the detection of abnormal areas in the coal seam’s roof and floor. Then, an optimization model is constructed with the objective of minimizing the amount of rock spoilage and missed coal, subject to the constraints of the mining equipment’s passability and posture limitations within the cutting space. NSGA-II algorithm is used to solve for the optimal cutting path. The simulation results show that, after optimization, the overall overall gangue cutting rate is 0.11%, and the coal recovery rate can reach 99.78%. The cutting planning path for the coal seam top and bottom plates is smooth and reliable. In areas with faulted geology, the planned cutting paths along the working face and the direction of the working face advancement effectively eliminate faulting phenomena. The deployment posture of the fully mechanized mining equipment have been significantly improved. The maximum vertical curvature of the scraper conveyor’s central trough is reduced from 18° to 2.5°, the pitch angle range of the hydraulic supports is optimized from −10°−35° to −12°−8°, the roll angle range of the hydraulic supports is optimized from 0°−25° to−4°−12°, the spacing range between the hydraulic support beams is optimized from −0.7−0.8 m to 0−0.18 m, the pitch angle of the hydraulic support beams is optimized from −20°−20° to −4°−4°, and the tilt angle of the hydraulic supports is optimized from −40°−40° to −5°−2°. The proposed method enables the cutting path planning for coal mining machines based on a three-dimensional geological model, effectively improving the coal recovery rate, reducing rock spoilage, and enhancing the adaptability of fully mechanized mining equipment in the cutting space. This method provides a valuable technical approach for the efficient and continuous operation of intelligent fully mechanized mining faces.